High-impact Routines to Ameliorate Trunk and Lower Limbs Flexibility in Women - De Nardi, Massimo; Facheris, Carlo; Ruggeri, Piero; La Torre, Antonio; Codella, Roberto (International Journal of Sports Medicine, 2020)
Several types of routines and methods have been experimented to gain neuro/muscular advantages, in terms of overall range of motion, in athletes and fitness enthusiasts. The aim of the present study was to evaluate the impact of different routines on trunk- and lower limbs flexibility in a sample of young women. In a randomized-crossover fashion, eleven subjects underwent to: hamstrings stretching [S]; hamstrings stretching plus whole-body vibration [S+WBV]; partial-body cryotherapy [Cryo]; rest [Control]. Standing hamstrings stretch performance and sit-and-reach amplitude resulted to be improved with [S+WBV] compared to all other protocols (p<0.05). [Cryo] ameliorated the active knee extension performance with respect to all other interventions (p<0.05). These flexibility improvements were obtained without a loss in the trunk position sense proprioception. These results represent the first evidence that a single session of either vibration or cryotherapy can ameliorate flexibility without losing the trunk position sense proprioception in young women.
Keywords: cryotherapy; whole-body vibration; standing hamstrings stretch